Pengaruh Penggunaan Metode PBL dalam Pembelajaran PKN Terhadap Peningkatan Skil Berfikir Kritis Terhadap Siswa Kelas 3 di SD - Arni, Yusnin; Hanipah, Hanipah; Elpiana, Elpiana; Luwinza, Mutiya (Invention: Journal Research and Education Studies, 2025)
This study aims to test the effect of the Problem Based Learning learning model in improving the critical thinking skills of grade 3 students in elementary school. While the theory used is the constructivist theory with observation data collection techniques from teacher and student activities and also using tests to test students' thinking skills. This study uses a quantitative approach with a quasi-experimental research method and a pretest-posttest control group design. The results showed that the average activity of the control class teacher was 74.99, while in the experimental class it was 84.37. The learning outcomes of students in the control class showed no significant results because they were less than 0.005. While in the experimental class showed significant results. Thus it can be concluded that the Problem Based Learning learning model is able to improve the critical thinking skills of grade 3 students in elementary school.